2012
DOI: 10.3892/ijmm.2012.899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hot water extract of Chlorella vulgaris on proliferation of IEC-6 cells

Abstract: Abstract. Chlorella vulgaris, a unicellular microalgae, exerts various biological effects; however their effect on proliferation signaling pathways in normal cells has not been studied. We investigated the effect of hot water extracts of Chlorella vulgaris (CVE) on cell proliferation and related signaling pathways in rat intestinal epithelial cells (IEC-6). CVE increased the expression of insulin-like growth factor-I receptor (IGF-IR) and the phosphorylation of focal adhesion kinase (FAK) and Src. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…At low concentrations, CGF induced cell proliferation with a maximum increase in cell viabilities at E max of 0.001 g/L for all cell types. This is in good agreement with previous studies which have shown that extracts of C. vulgaris are cell proliferative at lower concentrations while being cytotoxic at high concentrations ( Yusof et al, 2010 ; Song et al, 2012 ). In addition, our study revealed that variable cytotoxicity was observed amongst mammalian cell lines, with HDF displaying the highest sensitivity with an average CC 50 value of 0.597 g/L (95% CI: 0.508–0.710) and ADSC displaying the lowest sensitivity at CC 50 value of 4.645 g/L (95% CI: 2.932–7.172) ( Supplementary Table S2 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At low concentrations, CGF induced cell proliferation with a maximum increase in cell viabilities at E max of 0.001 g/L for all cell types. This is in good agreement with previous studies which have shown that extracts of C. vulgaris are cell proliferative at lower concentrations while being cytotoxic at high concentrations ( Yusof et al, 2010 ; Song et al, 2012 ). In addition, our study revealed that variable cytotoxicity was observed amongst mammalian cell lines, with HDF displaying the highest sensitivity with an average CC 50 value of 0.597 g/L (95% CI: 0.508–0.710) and ADSC displaying the lowest sensitivity at CC 50 value of 4.645 g/L (95% CI: 2.932–7.172) ( Supplementary Table S2 ).…”
Section: Resultssupporting
confidence: 93%
“…Table 1 shows the proximate crude composition of CGF. The soluble extract contained approximately 67.1% crude protein, 27.4% carbohydrate, and 5.7% crude ash, which is in good agreement with a previous study ( Song et al, 2012 ). In addition, the trace metals and microbial contents of CGF were found to be within the prescribed limits according to Singapore Medicines Act for human usage ( Koh and Woo, 2000 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Cell proliferation is induced through intracellular signal transduction mediated by receptor tyrosine kinases (RTKs), such as epidermal growth factor receptor (EGFR) (8). RTKs are cell membrane receptors for growth factors and other extracellular ligands.…”
Section: Introductionmentioning
confidence: 99%
“…3B ) expression levels of IGF-IR, IRS-1, Shc and PY-99. IGF-IR stimulates the proliferation of various cell types and inhibits apoptosis ( 25 ).…”
Section: Resultsmentioning
confidence: 99%